Changes of Sleep Structure in Rats after Artificial Hypometabolic State - Shilo, A. V.; Ventskovska, O. A.; Babiychuk, G. A. (Problems of Cryobiology and Cryomedicine, 2010)
The influence of artificial hypometabolic state (AHMS) on slow wave sleep (SWS) and paradoxical sleep (PS) occurrence and their daily distribution was studied. Awaking from AHMS was accompanied by total sleep deprivation with the following compensatory increase in SWS and PS amounts. Moreover AHMS caused no prolonged or stable changes in the sleep-wake cycle and did not effect daily total sleep duration. Sleep structure and sleep cyclicity were restored within 24 hrs.